Response Inhibition and Interference Suppression in Individuals With Down Syndrome Compared to Typically Developing Children - Traverso, Laura; Fontana, Martina; Usai, Maria Carmen; Passolunghi, Maria C. (Frontiers in Psychology, 2018)
The present study aims to investigate inhibition in individuals with Down Syndrome compared to typically developing children with different inhibitory tasks tapping response inhibition and interference suppression. Previous studies that aimed to investigate inhibition in individuals with Down Syndrome reported contradictory results that are difficult to compare given the different types of inhibitory tasks used and the lack of reference to a theoretical model of inhibition that was tested in children (see Bunge, Dudukovic, Thomason, Vaidya, & Gabrieli 2002; Gandolfi, Viterbori, Traverso, & Usai, 2014). Three groups took part in the study: thirty-two individuals with Down Syndrome (DS) with a mean age of 14 years and 4 months, thirty-five typically developing children five years of age (5TD), and thirty typically developing children six years of age (6TD). No difference emerged among the groups in fluid intelligence. Based on a confirmatory factor analysis, two different inhibition factors were identified (response inhibition and interference suppression), and two composite scores were calculated. An ANOVA was then executed with the composite inhibitory scores as dependent variables and group membership as the between-subject variable to explore the group differences in inhibition components. The 6TD group outperformed the 5TD group in both response inhibition and interference suppression component scores. No differences were found in both inhibition components between the DS group and 5TD. In contrast, the 6TD group outperformed the DS group in both response inhibition and in the interference suppression component’s scores. Summarizing, our findings show that both response inhibition and interference suppression significantly increased during school transition and that individuals with DS showed a delay in both response inhibition and interference suppression components compared to typically developing six-year-olds, but their performance was similar to typically developing five-year-olds.